Tool for enhancing social inclusion through local dialogues on natural resource management - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The tool was piloted in various contexts and natural resource management settings: community-based forest management in Karnataka, India; native fruit tree management in Sarawak, Malaysia; and community-based small water reservoir management in Boulgou, Burkina Faso.